(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Nursing education is a challenging process that merges knowledge and practices to prepare nurses to deal with life and death situations in a complex and challenging environment. Therefore, nursing students need to be motivated to progressively advance their academic and professional performance to meet the demand of the nursing profession. Objectives: This study aimed to investigate how students perceive the motivational level during their studies and the correlation between motivation and students' academic performance profiles in Jordan. Methods: Descriptive correlational research was used. A convenient sample of 335 students was recruited from selected nursing colleges in Jordan to answer a self-administered questionnaire. A self-administered questionnaire, "Effect of motivation on the health of College Students,” was used to answer the research questions. Statistical analyses were performed using SPSS (version 22). Frequency or percentage was used to analyze the demographic profile, and Spearman's rho correlation test was used to determine the correlations. Results: The overall mean of motivational factors among students was high, 3.69, and the highest five motivators were When the student finds the material to be stimulating and practical, the class is easy, and the student can get high scores, the midterms and finals are imminent, the average in the class is high, and when the student like the professor, with means of 4.65, 4.43, 4.37, 4.37, and 4.22 respectively. There was a significant positive correlation (significant 0.04) between the student's academic performance and motivational factors. Conclusion: This study helps administrators of colleges of nursing and health to identify motivating factors and practice implementing them to support psycho-academic conciliators. Accordingly, it may help create an academic environment that initiates students' efficiency, competency, and professionalism.